Ferroelectric low-voltage ON/OFF switching of chiral benzene-1, 3, 5-tricarboxamide derivative. Issue 30 (8th July 2020) - Wu, Jianyun; Takeda, Takashi; Hoshino, Norihisa; Akutagawa, Tomoyuki
Abstract : Chiral liquid crystalline benzene trialkylamide derivative showed much lower coercive electric field for ferroelectric switching. Abstract : The phase transition behaviour, molecular assemblies, and dielectric responses of an N, N ′, N ′′-trialkylbenzene-1, 3, 5-tricarboxamide derivative bearing chiral ( S )-3, 7-dimethyloctyl chains ( S -3BC ) were compared with those of an N, N ′, N ′′-trioctadecylbenzene-1, 3, 5-tricarboxamide derivative (3BC ) bearing achiral –CONHC14 H29 chains. Chiral S -3BC showed a similar phase transition behaviour to achiral 3BC, and ferroelectric polarization–electric field ( P – E ) hysteresis curves were observed in the discotic hexagonal columnar (Colh ) liquid crystal phase. Interestingly, the magnitudes of P r and E t values of S -3BC were 5.5-times larger and 13-times smaller than those of 3BC because of the introduction of the chiral alkyl chains, indicating a useful method to obtain low voltage ON/OFF ratios for the switching device. Much stronger N–H⋯O hydrogen-bonding interactions were observed in S -3BC than in 3BC because of much shorter π-stacking distance and blue-shift of the intermolecular asymmetrical N–H vibrational band in the former, which effectively decreased the potential energy barrier for the dipole inversion between N–H⋯O and O⋯H–N orientations and the E t value.